Dynasty Divided A Family History of Russian and Ukrainian Nationalism - Baumann, Fabian (NIU Series in Slavic, East European, and Eurasian Studies, 2023)
Dynasty Divided uses the story of a prominent Kievan family of journalists, scholars, and politicians to analyze the emergence of rivaling nationalisms in nineteenth-century Ukraine, the most pivotal borderland of the Russian Empire. The Shul'gins identified as Russians and defended the tsarist autocracy; the Shul'hyns identified as Ukrainians and supported peasant-oriented socialism. Fabian Baumann shows how these men and women consciously chose a political position and only then began their self-fashioning as members of a national community, defying the notion of nationalism as a direct consequence of ethnicity. Baumann asks what made individuals into determined nationalists in the first place, revealing the close link to private lives, including intimate family dramas and scandals. He looks at how nationalism emerged from domestic spaces, and how women played an important (if often invisible) role in fin-de-siècle politics.Dynasty Divided explains how nineteenth-century Kievans cultivated their national self-images and how, by the twentieth century, Ukraine steered away from Russia. The two branches of this family of Russian nationalists and Ukrainian nationalists epitomize the struggles for modern Ukraine.